Group Dynamics Effectiveness of Women’s Groups in Raipur District of Chhattisgarh - Dewangan, Payal; Vinayagam, S S; Shrivastava, K K (Indian Journal of Extension Education, 2020)
Women in formal groups show certain characteristics such as fellow feeling, co-operation, cordiality, sympathy, understanding, leadership, etc. among themselves. To utilize these potential quality attempts have been made for facilitating women’s overall status by organizing them into a formal group. The groups function to provide a platform for each member of the group to identify and use opportunities for their growth and empower WGs/ SHGs to collaborate with other institutions. Group dynamics is a phenomenon involving the group functions, its need, and the interaction among the members of the group. The research was performed in Raipur district ofÂ Chhattisgarh. Three villages were chosen from 2 selected blocks, and five women groups were selected from each village. A hundred and twenty respondents from thirty women groups were interviewed. Majority ofÂ respondents were found in medium category of group dynamics effectiveness dimensions such as participation, membership, influence, and style of influence, decision making procedure, task functions, maintenance functions, group atmosphere, interpersonal trust, norms, feelings and achievements in women’s group and most of them had empathy at lower category. Sixty-five percent of the women’s group had medium overall Group Dynamics Effectiveness (GDE) category.